The association between maternal-child physical activity levels at the transition to formal schooling: cross-sectional and prospective data from the Southampton Women’s Survey - Kathryn R. Hesketh; Soren Brage; Cyrus Cooper; Keith M. Godfrey; Nicholas C. Harvey; Hazel M. Inskip; Sian M. Robinson; Esther M. F. Van Sluijs (International Journal of Behavioral Nutrition and Physical Activity, 2019)
Abstract Background Physical activity decreases through childhood, adolescence and into adulthood: parents of young children are particularly inactive, potentially negatively impacting their children’s activity levels. This study aimed to determine the association between objectively measured maternal and 6-year-old children’s physical activity; explore how this association differed by demographic and temporal factors; and identify change during the transition to school (from age 4–6). Methods Data were from the UK Southampton Women’s Survey. Physical activity of 530 6-year-olds and their mothers was measured concurrently using accelerometry for ≤7 days. Cross-sectionally, two-level mixed-effects linear regression was used to model the association between maternal-child daily activity behaviour at age 6 [minutes sedentary (SED); in moderate-to-vigorous physical activity (MVPA)]. Interactions with demographic factors and time of the week were tested; how the association differed across the day was also explored. Change in the association between maternal-child physical activity (from age 4–6) was assessed in a subset (n = 170) [outcomes: SED, MVPA and light physical activity (LPA)]. Results Mother-child daily activity levels were positively associated (SED: β = 0.23 [0.20, 0.26] minutes/day; MVPA: 0.53 [0.43, 0.64] minutes/day). The association was stronger at weekends (vs. weekdays) (interaction term: SED: βi = 0.07 [0.02, 0.12]; MVPA: 0.44 [0.24, 0.64]). For SED, the association was stronger for those children with older siblings (vs. none); for MVPA, a stronger association was observed for those who had both younger and older siblings (vs. none) and a weaker relationship existed in spring compared to winter. Longitudinally, the association between mother-child activity levels did not change for SED and LPA. At age 6 (vs. age 4) the association between mother-child MVPA was weaker across the whole day (βi: − 0.16 [− 0.31, − 0.01]), but remained similar at both ages between 3 and 11 pm. Conclusions More active mothers have more active 6-year-olds; this association was similar for boys and girls but differed by time of week, season and by age of siblings at home. Longitudinally, the association weakened for MVPA between 4 and 6 years, likely reflecting the differing activities children engage in during school hours and increased independence. Family-based physical activity remains an important element of children’s activity behaviour regardless of age. This could be exploited in interventions to increase physical activity within families.